Evaluasi Program Pengembangan Kapasitas Aparatur Pemerintah Desa (Suatu Kajian Pelatihan Penyusunan RPJM Desa dan RKP Desa Kabupaten Bojonegoro pada Balai Besar Pemerintahan Desa di Malang) - Sari, Yanuar Kartika; Sholihah, Qomariyatus; Wanusmawatie, Ike (Jurnal Ilmiah Administrasi Publik, 2022)
This study aims to (a) describe and analyze the impact that occurred on the Village Government Apparatus "Training for the Preparation of the RPJM Desa and RKP Desa Bojonegoro Local Government" on their performance after attending the training at the Village Government Center in Malang (b) Describe and analyze the follow-up carried out Balai Besar Pemerintahan Desa di Malang in evaluating training programs to develop the capacity of the Village Government Apparatus. The results showed that the four stages for evaluating the Kirkpatrick model namely evaluating reactions, learning, behavior and results showed a significant impact on developing the capacity of village government officials in the training. After the evaluation is carried out, of course there are things that need to be improved so that follow-up steps are needed. The follow-up shows the involvement of structural, functional, and implementing officials at the Village Administration Center in Malang which contains several core things, such as facilities and infrastructure, modules, training methods, and trainers.